Numerical Context and Time Perception: Contrast Effects and the Perceived Duration of Numbers. (January 2016) - Alards-Tomalin, Doug; Walker, Alexander C.; Kravetz, Alexa; Leboe-McGowan, Launa C.
In the current study, we examined how the contextual repetition of magnitude information presented in either symbolic (Arabic digits) or nonsymbolic (numerosities) formats impacted on the perceived duration of a later occurring target number. The results of the current study demonstrated a time-magnitude bias in which, on average, large magnitude target numbers were judged to last for longer durations relative to small magnitude target numbers, regardless of notation (symbolic number and numerosity). Furthermore, context effects were found, in which a greater discrepancy in the target's magnitude from the initial context led to longer perceived duration ratings. However, this was found to be asymmetrical, occurring only for large magnitude targets. Additionally, the type of context effect was shown to be determined by whether the context was presented in the same notation as the target or a different notation.